Effect of brushing on the surface properties of modified polyetheretherketone (PEEK) - Yildiz, Semsettin; Tekin, Bahar (Mosher and Linder, Inc, 2025)
Purpose: To evaluate the surface roughness (SR) and surface topography (ST) of mechanical brushing with pure-unfilled PEEK (U-PEEK) and PEEK materials with different contents [titanium-containing PEEK (T-PEEK), ceramic-modified PEEK (C-PEEK) and glass fiber-reinforced PEEK (G-PEEK). Methods: A total of 40 disc-shaped samples (10 mm × 2 mm) were obtained (n= 10) from each group (U-PEEK, T-PEEK, C-PEEK, G-PEEK). After sanding and polishing, a profilometer was used to analyze all discs' surface roughness (Ra). Qualitative analysis (QA) was performed on random samples with the help of a scanning electron microscope (SEM). Brushing was done with a custom-made brushing simulator, and the analyses were repeated. Statistical analysis was performed (P< 0.05). Results: A statistically significant difference was found between the PEEK groups before and after brushing (P< 0.05). In the measurements before and after brushing, the lowest measurement value was seen in the C-PEEK and T-PEEK groups. While there was no significant difference between T-PEEK and C-PEEK measurements, both measurements found the highest measurement value in the G-PEEK group. In addition, in all groups, the average roughness values after brushing were statistically significantly higher than those before brushing. All groups except G-PEEK are below the clinically acceptable SR value (0.2 ?m) before and after brushing. T-PEEK and C-PEEK show better SR values. © 2025 Mosher and Linder, Inc. All rights reserved.
Keywords: Benzophenones; Ceramics; Dental Materials; Glass; Humans; Ketones; Materials Testing; Microscopy, Electron, Scanning; Polyethylene Glycols; Polymers; Surface Properties; Titanium; Toothbrushing; benzophenone derivative; dental material; glass; glass fiber; ketone; macrogol derivative; polyetheretherketone; polymer; titanium; ceramics; chemistry; devices; human; materials testing; scanning electron microscopy; surface property; tooth brushing